Diseases of the respiratory system in patients with juvenile idiopatic arthritis - Tuszkiewicz-Misztal, Ewa; Postępski, Jacek; Zaorska-Rajca, Janina; Opoka-Winiarska, Violetta; Czekajska-Chehab, Elżbieta (Reumatologia/Rheumatology, 2005)
In contrast to adult rheumatoid arthritis little is known about the prevalence, nature and cause of lung function abnormalities in children with juvenile idiopatic arthritis (JIA). Pulmonary manifestation in children with JIA include recurrent pneumonia or pleuritis lymphoid follicular pneumonitis, pulmonary nodules and pulmonary hemosiderosis. Rheumatoid pulmonary vasculitis is rare. Pulmonary abnormal function test in some children, may be the results of respiratory muscle weakness. Pulmonary parenchymal involvement is very uncommon. The temporal relationship of the pulmonary and articular disease is variable. Pulmonary involvement in juvenile arthritis is mainly manifested by abnormal pulmonary function tests, including mild airflow limitation decreased lung volumes and abnormal diffusion capacity have also been reported in children with JIA, even in the absence of pulmonary symptoms. Pulmonary toxicity occurs in 0.5% to 14% of patients receiving low-dose Mtx. Manifestations of pulmonary toxicity and include parenchymal inflammation, pneumonia, airway hyperreactivity, air trapping and possibility of neoplasm.